2019
DOI: 10.24925/turjaf.v7i6.883-887.2451
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase, Specific Acetylcholinesterase and Total Protein Concentrations in the Brain Regions of Broiler Chickens Fed Dietary Monosodium Glutamate

Abstract: The study was carried out to examine the effect of varied levels of dietary monosodium glutamate on acetylcholinesterase, specific acetylcholinesterase and total protein concentrations in the brain regions of broiler chickens. Three hundred (300) day – old unsexed Abor – acre chickens were randomly assigned to diets: A, B, C, D, E and F containing 0.00, 0.25, 0.50, 0.75, 1.00 and 1.25 g/kg MSG respectively. Each treatment was replicated 5 times with 10 birds per replicate. The birds were fed ad – libitum and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…This action could promote cholinergic neurotransmission and thus availability of acetylcholine at the synapse [19]. The insignificant effect in the AChE activities of the pineal body of the broiler chickens showed that dietary Ficus carica and vitamin C at the supplemental levels as well as the interaction of the two treatments and levels did not interfere with melatonin production thereby did not affect negatively the modulation of sleeping pattern and behavior of the birds [20]. Moreso, the significant effect of the activities of the AChE of the olfactory lobes of the broilers indicated that their sense of smell was not also negatively affected by the interactions which are attributed to the fact that birds have the least sense of smell and do not use smell extensively to make most of their decisions [21].…”
Section: Growth Hormone Of Broiler Chicken Fed Ficus Carica and Vitam...mentioning
confidence: 99%
“…This action could promote cholinergic neurotransmission and thus availability of acetylcholine at the synapse [19]. The insignificant effect in the AChE activities of the pineal body of the broiler chickens showed that dietary Ficus carica and vitamin C at the supplemental levels as well as the interaction of the two treatments and levels did not interfere with melatonin production thereby did not affect negatively the modulation of sleeping pattern and behavior of the birds [20]. Moreso, the significant effect of the activities of the AChE of the olfactory lobes of the broilers indicated that their sense of smell was not also negatively affected by the interactions which are attributed to the fact that birds have the least sense of smell and do not use smell extensively to make most of their decisions [21].…”
Section: Growth Hormone Of Broiler Chicken Fed Ficus Carica and Vitam...mentioning
confidence: 99%
“…The experimental feeds were prepared in Evan Company and contained starter (1-10), grower (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and finisher (26-42) days: 3097, 2990, and 2906 kcal/kg metabolizable energy, and 22.97, 21.50, and 20.78 % crude protein respectively. Chicks received 24 hours of light (L) during the 1 st week.…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…Body growth: Body weight, weight gain, feed intake, Feed Conversion Ratio (FCR), mortality and feasibility were measured during 42 days according to Olarotimi, and Adu [14].…”
Section: Study Area and Experimental Designmentioning
confidence: 99%